Between illiberalism and hyper-neoliberalism: competing populist discourses in the Czech Republic - Seongcheol Kim (European Politics and Society, 2020)
This paper draws on Laclau's theory of discourse, hegemony, and populism to analyse competing forms of populism in the Czech Republic within the discursive context of `post-November transformation' as well as in relation to hegemonic struggles over the construction of social order. It is argued that the discourses of Public Affairs (VV), ANO, Dawn of Direct Democracy, and Freedom and Direct Democracy (SPD) all feature a populist opposition between the `people' or `citizens' on the one hand and `political dinosaurs', (`traditional') `parties', or `godfather party mafias' of both `left' and `right' on the other, while also radicalizing in different ways the exclusionary constructions of `work' in the established discourses of the Civic Democrats (ODS) and Social Democrats (ČSSD). While ANO constructs `hard work' in a populist manner against the (`traditional') `parties', VV and Dawn/SPD articulate an exclusion of non-working `unadaptables' that points to a notable interplay of hyper-neoliberal welfare chauvinism and anti-minorities illiberalism.
Keywords: 330; Czech Republic; illiberalism; neo-liberalism; party politics; populism